Pembelajaran Seni Gerak dan Seni Tari di PAUD Cerdas Ceria - Hilda Zahra Lubis; Dwi Nur Attira Ain; Nabila Nabila; Salsabila Salsabila (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This article discusses the implementation of movement and dance arts learning in Smart and Cheerful PAUD as an effort to optimize early childhood development. Movement and dance arts activities have been proven to have a positive impact on gross and fine motor skills, creativity, social-emotional, and children's self-expression. This study used observation and ability test methods on children's participation in art activities. The results showed that most children were able to follow simple dance movements, recognize musical rhythms, dare to perform, and demonstrate good body coordination. Movement and dance arts learning not only supports physical and emotional growth, but also strengthens children's love for local culture. Therefore, movement and dance arts need to be made an integral part of the PAUD curriculum in a structured and enjoyable way, so that they can have a holistic impact on children's development.